Triple IgE-positivity to hornet, wasp and bee venom in the patient with anaphylaxis: diagnostic and therapeutic approach - Jovanović, Dragana R; Perić-Popadić, Aleksandra; Andrejević, Sladjana; Jovanović, Igor; Bonači-Nikolić, Branka (Vojnosanitetski pregled, 2021)
Abstract Introduction. Triple-positivity (TP) or double-positivity (DP) for serum-specific immunoglobulin E (sIgE) antibodies against hornet venom (HV), wasp venom (WV) and/or honeybee venom (BV) causes significant problem in a selection of appropriate venom immunotherapy. However, DP/TP can be caused by cross-reactions resulting either from partial sequence identity of protein allergens in the venoms, or may be related to cross-reacting carbohydrate determinants (CCDs). Case report. A 60-year-old man was stung by a wasp and two days later by hornet. In both cases, within 15 minutes he developed hypotension and generalized urticaria and he was successfully treated with epinephrine, corticosteroids and fluids. After eight weeks, the examination revealed the negative skin prick test for all three venoms, but the sIgE-determination (ELISA, Biopharm) showed triple sensitization to native BV (0.55 IU/mL), WV (3.35 IU/mL) and HV (0.37 IU/mL). He was receiving the venom immunotherapy with venom mixtures for one year. In order to distinguish true multiple sensitization from cross-reactivity, the molecular-allergy testing by ImmunCAP with the CCD-free recombinant major allergens was performed. A high sensitization to Antigen 5-rVes v5 of WV (31.4 kU/L) was demonstrated while sIgE to phospholipase A2-rApi m1 of BV (0.15 kU/L) was negative; sIgE to CCD-MUXF3-bromelain (0.75 kU/L) explained the sIgE-positivity for native BV. After these findings, a venom immunotherapy only with WV was initiated. Conclusion. In our patient, triple-IgE-positivity to native venoms detected by the ELISA was caused by cross-reactivity to CCDs. We recommend the molecular-allergy testing with the nonglycosylated recombinant allergens before starting the venom immunotherapy in patients with multiple-sIgE-positivity to native Hymenoptera venoms.
Keywords: anaphylaxis; bites and stings; cross reactions; desensitization, immunologic; hymenoptera; venoms